Evaluation of Learning Content Standards at Autistic Schools in Surakarta - Gangsar Ali Daroni; Munawir Yusuf; Zaini Rohmad; Gunarhadi Gunarhadi; Edy Legowo (Journal of ICSAR, 2019)
This research is aimed at evaluating the learning content standard of special schools for autistic students at the elementary level in Surakarta. Data were collected using questionnaires. Interviews and observations were conducted to obtain qualitative data in support of the quantitative data. The quantitative data were analyzed using descriptive statistical analysis. The results showed that the implementation of learning content standards for autistic schools in Surakarta is in a very good category with the average percentage of 81%. However, the implementation of the standards still faces obstacles; therefore it needs some adjustments with the new curriculum (2013 Curriculum). These results can be used as suggestions to improve the implementation of content standards for autistic school in Surakarta.